2009
DOI: 10.1590/s0102-09352009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de leishmaniose tegumentar em cães de área endêmica no Estado do Paraná

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Large numbers of dogs seropositive for Leishmania spp. have been documented in this state, with a rate of 38.73% (67/173) recorded in the municipality of Umuarama (GERÔNIMO et al, 2014), 18.2% (24/132) in Jussara and Terra Boa (SILVEIRA et al, 1996), 19% (24/126) in Mariluz (LONARDONI et al, 2006), 6.6% (11/169) in Cianorte (CERINO et al, 2010), 45.4% (222/489) in Bela Vista do Paraíso (REIS et al, 2011), and 55.2% (37/67) (ZANZARINI et al, 2005) and 24% (12/50) (PITTNER et al, 2009) in the Maringá region. Such high estimates stress that elevated seropositivity is due to the region's ecosystem and its status as an area endemic for American CL in humans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large numbers of dogs seropositive for Leishmania spp. have been documented in this state, with a rate of 38.73% (67/173) recorded in the municipality of Umuarama (GERÔNIMO et al, 2014), 18.2% (24/132) in Jussara and Terra Boa (SILVEIRA et al, 1996), 19% (24/126) in Mariluz (LONARDONI et al, 2006), 6.6% (11/169) in Cianorte (CERINO et al, 2010), 45.4% (222/489) in Bela Vista do Paraíso (REIS et al, 2011), and 55.2% (37/67) (ZANZARINI et al, 2005) and 24% (12/50) (PITTNER et al, 2009) in the Maringá region. Such high estimates stress that elevated seropositivity is due to the region's ecosystem and its status as an area endemic for American CL in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Dogs can harbor high levels of parasitism, favoring infection of sand flies (DINIZ et al, 2008). The role of canines in the CCL chain of infection remains an active area of research; however, it has been observed that in areas endemic for the human form of this disease, dogs are also infected with protozoa (FALQUETO et al, 1986;PITTNER et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zulpo et al (2012) and Caldart et al (2015) studied animals from Londrina and found 11.6% (13/112) and 1.2% (3/236) of seropositivity using IFAT method with 1:40 as a cutoff, respectively; the low prevalence of 1.2% found by the authors may be explained because this study population consisted of clinically healthy animals undergoing elective castration surgery. Pittner et al (2009) (CASTRO et al, 2007;PEREIRA, 2005, HOFFMANN et al, 2012. Several phlebotomine species are present in the same State, and the dominant vector species found infected is Nyssomyia whitmani (MEMBRIVE et al, 2004;OLIVEIRA et al, 2000) wich is involved in the transmission of L. (V.) braziliensis; however, L. (L.) amazonensis vectors have never been found in Paraná.…”
Section: Discussionmentioning
confidence: 99%
“…O papel do cão na transmissão da LV é bem conhecido, sendo estes animais considerados o principal reservatório da infecção para os humanos (ALVAR; YACTAYO;BERN, 2006). Dentro da cadeia epidemiológica da leishmaniose cutânea o papel do cão é ainda objeto de estudo, no entanto, observa-se que nas áreas endêmicas os cães também apresentam infecção pelo protozoário (FALQUETO et al, 1986;PITTNER et al, 2009).…”
Section: Introductionunclassified